Analisis Penerapan Akuntansi Aset Tetap Menurut PSAP No. 07 Pada Dinas Tenaga Kerja Provinsi Sumatera Utara - Aftiah, Nurul; Harmain, Hendra; Atika, Atika (Universitas Labuhanbatu, 2023)
This study aims to analyze the application of fixed asset accounting according to PSAP 07 at the Sumatera provincial Manpower office whether it is in accordance with government accounting standards that have been implemented and to know how the recognition of the granting of rights to use fixed assets according to PSAP 07. The approach of this study is a descriptive approach, namely research conducted by collecting and presenting data received from the Sumatera provincial Labor Office in the form of Financial Statement data , recapitulation of depreciation of Fixed Assets, Inventory card list of goods and then the results of interviews are quite clear researchers analysis and compare with existing theories and Government Accounting Standards PSAP 07. The results showed the recognition of fixed assets on land and the condition of assets that are still not in accordance according to PSAP 07, owned land is not intended to be sold but used for agencies. This is due to a lack of understanding of fixed assets according to PSAP 07 which is very necessary for accountability reports in accordance with Government Accounting Standards that have been established and implemented.